2002
DOI: 10.1016/s0378-4371(01)00506-4
|View full text |Cite
|
Sign up to set email alerts
|

Transport theory in the context of the normalized generalized statistics

Abstract: In this work assuming valid the equipartition theorem and using the normalized q-expectation value, we obtain, until first order approximation, the hydrodynamics equation for the generalized statistics. This equations are different from those obtained in the context of the Boltzmann-Gibbs statistics. This difference is that now appears two transport coefficient that depend on the q-value. PACS number(s): 05.20.Jj, 05.20.Gg

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 10 publications
(14 reference statements)
3
17
0
3
Order By: Relevance
“…This additional term was also found by Boghosian and by Potiguar and Costa [2,3] in the derivation of the Navier Stokes equations for Tsallis thermostatistics, and is the only additional term allowed by the Curie principle.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…This additional term was also found by Boghosian and by Potiguar and Costa [2,3] in the derivation of the Navier Stokes equations for Tsallis thermostatistics, and is the only additional term allowed by the Curie principle.…”
Section: Introductionsupporting
confidence: 66%
“…Boghosian found that the incompressible limit of the Navier-Stokes equations is independent of the parameter q characterizing the Tsallis distribution, whereas the energy equation in the compressible case contains an additional q-dependent contribution to the heat flux [2]. This result was confirmed in [3], and the additional term is the only further term allowed by the Curie principle [12].…”
Section: Introductionmentioning
confidence: 94%
“…It is interesting to compare our results (and the overall approach) with independent analyzes and some previous expressions to nonextensive transport coefficients appearing in the literature [7,10]. We first notice that our main results are quite different from that ones obtained by Boghosian [7].…”
Section: Discussionmentioning
confidence: 50%
“…32 Similar fluid equations have been found from other transport models within q-statistics. 25,51 The first order solution of Eq. (38) is determined following the standard procedure of Refs.…”
Section: Chapman-enskog Methodsmentioning
confidence: 99%